The First and the Last Emigration: A Comparison - Dąbrowski, Mieczysław (Porównania, 2022)
The article “The First and the Last Emigration” is an attempt to describe the differences and similarities between the first wave of economic emigration from the late nineteenth century and a similar wave from the end of the 20th century, increased in 2004 after Poland joined the European Union. On the basis of literary texts - in the first case by the main positivist writers, and in the second by numerous texts written by migrants themselves - the author examines issues such as the place and function of religion in emigrant circles, the categories of patriotism, xenophobia, tribalism, language and identity of emigrants.